Navigating Graduate Education in an Era of Policy-Driven Employment Pressures. - Ahmed, Fauwad (American Journal of Public Health, 2026)
The article tackles the difficulties faced by student professionals in navigating graduate education in an era of policy-driven employment pressures. Topics discussed include threat posed by the Obe Nig Beautiful Bill Act, funding cuts and structural barriers to graduate public health training, psychological toll of policy changes on student well-being and its equity implications, and the need for multisectoral effort to support the next generation of public health professionals.